VHMS deposit models for the Cordillera Real divisions: Alao and Salado - Calero-Gómez, Kevin (2021)
The Cordillera Real comprises autochthonous and allochthones land accreted to the continent, represented from west to east by thelithothectonic divisions Guamote, Alao, Loja, Salado and Zamora Divisions. (Litherland, et al. 1994). This work describes the possible VHMS (Volcanogenic Massive Sulphide) deposits present in the Alao and Salado divisions, based on previous studies of petrology, petrography and evolution of these divisions. The parameters used to compare VHMS model types with possible deposits of the divisions are: geological environment, tectonic framework, nesting rocks, associated rocks, textural and mineralogical characteristics of massive bodies, alteration and geochemical characteristics. In this way, it can be established that the deposits of the Peltetec Unit are not associated with a VHMS deposit as there are differences with respect to lithology and geochemistry. In contrast, the model associated with a Kuroku-type VHMS deposit coincides with the characteristics of a VHMS deposit in the Alao-Paute Unit. In turn, deposits from the Salado Division were associated with a Besshi-type VHMS deposit, finding similarities in terms of the geological-tectonic environment, mineralogy and similarity of the geochemical traces, however, the formation and evolution characteristics of the Salado Division has hindered the full development of these Besshi-type VHMS, but their existence is not ruled out.